2020
DOI: 10.3390/antiox9050436
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Biological Activities of Fruits and Leaves of Elaeagnus multiflora Thunb. and Their Isoprenoids and Polyphenolics Profile

Abstract: The objective of this study was in-depth identification of carotenoids and polyphenolic compounds in leaves and fruits of Elaeagnus multiflora Thunb. An additional aim was to assay their antioxidant and in vitro biological activities (the ability to inhibit pancreatic lipase, α-amylase, and α-glucosidase activity) of two cultivars: ‘Sweet Scarlet’ and ‘Jahidka’. Study results showed the presence of 70 bioactive compounds, including 20 isoprenoids and 50 polyphenols. The profile of identified bioactive compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 59 publications
4
19
2
Order By: Relevance
“…The extraction and measurement of procyanidins by the phloroglucinol test were performed according to the method by Lachowicz et al [7]. Phloroglucinolysis was analyzed using a liquid chromatograph (Waters, Milford, MA, USA) consisting of a diode array, scanning fluorescence detectors, and a column manager.…”
Section: Determination Of Procyanidins By the Phloroglucinolysis Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The extraction and measurement of procyanidins by the phloroglucinol test were performed according to the method by Lachowicz et al [7]. Phloroglucinolysis was analyzed using a liquid chromatograph (Waters, Milford, MA, USA) consisting of a diode array, scanning fluorescence detectors, and a column manager.…”
Section: Determination Of Procyanidins By the Phloroglucinolysis Methodsmentioning
confidence: 99%
“…The homogeneous dry material was obtained by crushing the dried tissues using a closed laboratory mill (IKA A.11; Darmstadt, Germany). The powders were kept in a refrigerator (−80 • C) until extract preparation [7].…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Elaeagnus multiflora fruit (EMF) is edible and used in small amounts in herbal medicines, particularly owing to its anticancer and antioxidant activities [12,13]. Furthermore, the EMF contains multiple compounds and has numerous physiological effects [14][15][16][17]. We previously reported that the EMF extracts have antifatigue effects [18].…”
Section: Introductionmentioning
confidence: 99%